Prognostic factors in hypertrophic cardiomyopathy in children: An MRI based study. (1st October 2022) - Ali, Lamia Ait; Marrone, Chiara; Martins, Duarte Saraiva; Khraiche, Diala; Festa, Pierluigi; Martini, Nicola; Santoro, Giuseppe; Todiere, Giancarlo; Panaioli, Elena; Bonnet, Damien; Boddaert, Nathalie; Aquaro, Giovanni Donato; et al.
Abstract: Background: Clinical and prognostic role of cardiac magnetic resonance (CMR) in adult population with hypertrophic cardiomyopathy (HCM) have been largely assessed. We sought to investigate the role of CMR for predicting cardiovascular events in children with HCM. Methods: CMR was performed in 116 patients with HCM (37 sarcomeric mutations, 31 other mutations, mean age 10.4 ± 4.3 yrs). CMR protocol included cine imaging for evaluation of morphology and function and late gadolinium enhancement (LGE). Hard cardiac events (sustained VT, resuscitated cardiac arrest, sudden cardiac death, end-stage heart failure, heart transplant and appropriate ICD intervention) were recorded through a median follow-up of 4 (1–7) years. Results: During follow-up 21 heart cardiac events occurred. At maximal-rank statistic the optimal cut-point for LGE extent for predicting events was ≥2%. Syncope, non-sustained ventricular tachycardia (NSVT) and LGE extent ≥2% were independent predictors of events. At Harrel's C statistic combination of LGE extent ≥2% and syncope was the strongest model for predicting events. HR of patients with LGE extent ≥2% and no history of syncope was 3.6 (1.1–12.2) that increased to 37.6 (5.4–161) in those with LGE extent ≥2% and syncope. The median time dependent AUC of LGE extent (0.88, 95% CI 0.86–0.89) was significantly higher than that of syncope (0.63, 95% CI 0.61–0.66, p < 0.0001) and NSVT (0.52, 95% CI 0.50–0.53, p < 0.0001). Conclusions: In children with HCM, LGE and syncope were independent predictors of hard cardiac events at follow-up. Highlights: We present the results of a multicentric pediatric cohort of HCM submitted to CMR with a median follow-up of 4 years. Syncope, non-sustained ventricular tachycardia (NSVT) and LGE extent ≥2% were independent predictors of events. Combination of LGE and syncope was the best model for predicting events. LGE extent alone was the strongest predictor.